Measuring qol in Doğanbey urban trasformation area in Bursa, Turkey - Gür, Miray; Taneli, Yavuz; DOSTOĞLU, NESLİHAN (My University, 2019)
This study aims to measure the quality of life (QoL), using the proposed conceptual model within the context of the interactions between human behaviour and the environment. It aims to research the effect of the control of residents on QoL, and the findings constitute the basis for a discussion on the effects of environmental policies on QoL. Doganbey in Bursa, which is in close proximity to the Khans (Inns) District, is selected as the study area because it represents an urban transformation implemented according to administrative decisions. QoL measurements in the research reflect people's evaluations, their adaptation to post-transformation environment and the implementation process by means of questionnaires and in-depth interviews. The findings indicate that lack of resident control has an adverse effect on satisfaction and QoL, and that an urban transformation conducted without user participation will fail. In conclusion, the study aims to contribute to decision-making mechanisms within the framework of residents' influence to ensure increased QoL. The intention of the authors is to promote the usage of QoL scale developed for other housing or transformation areas by modifying the questions according to varying geographies and social groups.
Keywords: Quality of Life; Resident Satisfaction; Urban Transformation; Doganbey; Resident Control; Participatory Design; Yaşam Kalitesi; Yerleşik Memnuniyeti; Kentsel Dönüşüm; Doğanbey; Yerleşik Kontrol; Katılımcı Tasarım